South Sanctum of Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
To the south of the mandapa (pillared hall) lies a shrine with an intricately carved, multi-shakha (vertical bands or architraves) doorframe. The doorframe contains niches adorned with Shiva and his manifestations, Matrikas and Ganesh. The lalatabimba (lintel) is covered in white paint, obscuring its details. In the garbhagriha (sanctum), a Shiva linga is placed.